Agrobacterium-опосередкована трансформація м’якої пшениці з використанням калюсних культур - Бавол, А.В.; Дубровна, О.В.; Гончарук, О.М.; Воронова, С.С. (Фактори експериментальної еволюції організмів, 2014)
Aims. Agrobacterium-mediated transformation of morphogenic calli of wheat and optimization of stages of its implementation. Methods. For transformation we аre use calli induced from apical meristems of 3-day seedlings. Results. Morphogenic calli of bread wheat (Triticum aestivum L.) cv Podolyanka were transformed using Agrobacterium tumefaciens strains carrying binary vector pCB002 (with the genes gus and nptII) or pBi2E (pdh genes and nptII). Conclusions. It is shown that the optimal conditions for transformation is: concentration of agrobacteria OD = 0.2, cocultivation period of calli and agrobakteria for 3 days and the use of antibiotic cefotaxime at a concentration of 250 mg/l. Under these conditions, 54% of calli kept morphogenic potential. We found different sensitivity of cv Podolyanka to the Agrobacterium strains/genetic constructions.

Key words: Triticum aestivum L., Agrobacterium-mediated transformation, wheat.